The impact of unconventional monetary policy tools on the independence of the central bank (case study of the FED) - azzeddine ouadi; sadia hadiouche (Journal of Excellence for Economics and Management Research, 2022)
The importance of the study is highlighted by the significant and effective role played by the independence of the Central Bank in achieving the effectiveness of monetary policy. The failure of the Central Bank to be subject to political considerations and interventions will increase the transparency and credibility of monetary policies. For different countries and the emergence of modern trends in their independence, as well as the importance highlights by presenting the experience of the FED, which is considered among the most important central banks that was able to withstand the financial crisis in front of modern trends, whether in its monetary policy or its independence. Our study concluded that following monetary policies is not This traditionally leads to restricting the independence of the central bank, and this is what was shown in the FED.